Interventional cytology benefits patients undergoing thyroid FNA. Issue 4 (30th September 2022) - Vohra, Poonam; Khanafshar, Elham; Balassanian, Ron
Abstract : Rapid onsite evaluation (ROSE) plays a role in preventing unnecessary surgery and will ultimately reduce the financial burden on the health care system. Data from retrospective studies supports offering interventional cytology and ROSE as the standard of care for patients undergoing thyroid fine‐needle aspiration biopsy.